DESIGN OF 8-STOREY RESIDENTIAL BUILDING IN CORPUS CHRISTI, TEXAS, USA - Kudaibergenov, Sagidolla; Sanat, Sanzhar; Pernebay, Damir; Balkibekova, Kamila; Shyntas, Kuanysh; Yersainov, Zhanbolat; Zhakeshova, Amira (Nazarbayev University School of Engineering and Digital Sciences, 2025)
This project focuses on the design of an 8-story residential building with integrated commercial spaces and office units located in Corpus Christi, Texas, USA. The city's growing population and its diverse economy, influenced by tourism, healthcare, and energy sectors, have created a high demand for residential housing and new business infrastructure. The study provides a comprehensive analysis and design process, including architectural and structural elements, geotechnical considerations, environmental engineering, and construction management. All designs and calculations follow American building codes to ensure safety and reliability. This project aims to create a practical and well-designed building that meets the city’s housing and business needs.
Keywords: Structural engineering; Geotechnical engineering; TECHNOLOGY::Other technology::Environmental engineering; Residential building design; SAP2000; PLAXIS2D; PLAXIS3D; Foundation; type of access: embargo